KONTRIBUSI INISIASI MENYUSU DINI DAN DUKUNGAN SUAMI PADA RIWAYAT ASI EKSKLUSIF BAYI UMUR 6 SAMPAI 12 BULAN - Ika Putri Hasanah; Triska Susila Nindya (Universitas Airlangga, 2015)
World Health Organization (WHO) and United Nations Children’s Fund (UNICEF) provide recommendations for exclusive breastfeeding until the child aged 6 months and continued until the child aged 2 years. Exclusive breastfeeding has many benefits, however its practice remains low which can be caused by several factor, such as early initiation of breastfeeding and the husband support. This study aims to analyze the relationship between early initiation of breastfeeding and husband suppport with the exclusive breastfeeding history for infants aged 0 to 6 months old in the area of Brambang Public Health Center, Jombang district. The study design was cross sectional. The sample was mothers with infants aged 6 to 12 months as much as 77 respondents in area of Brambang Public Health Center, Jombang district. Subjects were taken using simple random sampling. Information in the study obtained through direct interviews with questionnaires to mothers. Chi-Square test was used to analyze the relationship between early initiation and the husband support with exclusive breastfeeding history. The result showed that there was a relationship between early initiation of breastfeeding (p=0,000) and husband support (p=0,000) with exclusive breastfeeding history. The result showed that early initiation of breastfeeding and husband support could increase the tendency of exclusive breastfeeding. It suggested to improve the early initiation of breastfeeding in maternity hospitals and improve husband support by involving husband during breastfeeding counseling.Keywords: Early initiation of breastfeeding, exclusive breastfeeding history, husband support